دراسة تحليلية عن خصائص القاموس الجيبي "نجوى الثريا في لسان أفصح البرايا" لمحمد إبراهيم، و جمال الدين متقين، و جابر عبد الرحمن - Chairunnisa Girsang, Alifia; Manik, Wagiman; Jamaluddin, Muhajirah (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
This research is a library research using the content analysis method. The objectives of this dictionary research are (1) To determine the characteristics of the Arabic pocket dictionary "Najwas Tsuraya fii Lisaani Afshahil Barayaa" by Muhammad Ibrahim, Jamaluddin Muttaqin, and Jabir Abdurrahman (2) To determine the advantages of the Arabic pocket dictionary Analysis of the Characteristics of the Arabic Pocket Dictionary "Najwas Tsuraya fii Lisaani Afshahil Barayaa" by Muhammad Ibrahim, Jamaluddin Muttaqin, and Jabir Abdurrahman (3) To determine the disadvantages of the Arabic pocket dictionary Analysis of the Characteristics of the Arabic Pocket Dictionary "Najwas Tsuraya fii Lisaani Afshahil Barayaa" by Muhammad Ibrahim, Jamaluddin Muttaqin, and Jabir Abdurrahman. Research results: The characteristics of this dictionary are that this dictionary is divided into three volumes based on classes or chapters whose words are arranged in tables, the vocabulary is written in singular and plural forms, the number of mufidah, and common expressions next to it. The advantages of this dictionary are its small size and light weight with a "pocket" shape, bookmarks from the dictionary publisher, there are names of types and plural forms at the end of the first volume. Some of the disadvantages of this dictionary are that it does not include the root word after the verb, does not include the command word after the verb, does not include antonyms after the word except for a few, and does not include synonyms after the word.